Educational Experience, Pedagogical Research and the State’s Interest - Hogan, Pádraig (Paedagogia Christiana, 2023)
This contribution makes the case that education has inherent purposes which distinguish it as a human practice; purposes that are distinct from those of the state. The philosophical and historical ancestry of these purposes is explored. This exploration reveals that educational experience is more properly understood as a live encounter with inheritances of learning than as a matter of transmission. The teaching of religion is taken as a concrete example to highlight this key difference. Where the state fails to recognise the inherent purposes of education, these purposes can become compromised. Accordingly, educational practice may fall victim to different kinds of domination. Some historical and more recent examples of such domination are identified and considered, as is an example of a healthy relationship between the state and educational practice. The consequences of the investigation for pedagogical research and practice, and for the proper relationship of the state to education, are then reviewed.